Anti-corrosion coating for cooling tower of power plant

Through the method of synergistic modification of sheet-shaped graphene oxide by silane coupling agent and polyetheramine, the problem of poor compatibility between nanofillers and epoxy resins is solved, and the corrosion resistance and impact resistance of anti-corrosion coatings in the cooling tower of the power plant is significantly improved. .

CN119432201APending Publication Date: 2025-02-14INNER MONGOLIA JINGDA POWER GENERATION CO LTD +1

Patent Information

Application Number
CN202411080966.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When existing epoxy resin coatings are used in cooling towers of power plants, the compatibility of nanofillers and epoxy resins is poor, resulting in uneven dispersion of fillers and weak binding force, which affects the modification effect.

Method used

The sheet-shaped graphene oxide is synergistically modified by silane coupling agent and polyetheramine. Through chemical reactions, strong chemical bonding is formed to improve the dispersion of nanofillers, and the modified graphene oxide is used as a filler to modify the water properties. Epoxy resin coating.

Benefits of technology

It improves the corrosion and impact resistance of the coating, enhances the compatibility and bonding of nanofillers with epoxy resins, and significantly improves the corrosion resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a power plant cooling tower anticorrosive coating which comprises a component A and a component B. The component A comprises bisphenol A type liquid epoxy resin, siloxane modified waterborne epoxy resin dispersion liquid, a modified amine curing agent, talcum powder, a dispersing agent, a flatting agent and titanium dioxide. The component B comprises a nano filler, a silane coupling agent and polyether amine; the component A and the component B are uniformly mixed according to the mass ratio of 1: (0.2-0.25). According to the invention, the silane coupling agent and the polyether amine are utilized to synergistically modify the flaky graphene oxide to improve the dispersity of the flaky graphene oxide, and the modified graphene oxide is used as a filler to modify the waterborne epoxy resin coating, so that the prepared coating has excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of anti-corrosion coating preparation, in particular to an anti-corrosion coating for a cooling tower of a power plant. Background Art

[0002] In the cooling tower of a power plant, metal corrosion seriously affects the service life of the cooling tower. Applying anti-corrosion coatings is an effective way to protect metal equipment and extend its service life. Epoxy resin coatings are one of the most widely used anti-corrosion coatings for metal equipment.

[0003] Nanofiller modification is one of the effective methods to improve the corrosion resistance and mechanical properties of epoxy resin coatings. The compatibility between nanofillers and epoxy resin is the key to the modification effect of nanofillers. Poor compatibility will lead to uneven dispersion of nanofillers in the epoxy resin system, and the bonding force between fillers and epoxy resin is weak after the coating is cured, which seriously affects the modification effect.

[0004] Therefore, there is a need for an anti-corrosion coating for cooling towers of power plants having high compatibility between nanofillers and epoxy resins. Summary of the invention

[0005] In view of this, the present invention aims to provide an anti-corrosion coating for a cooling tower of a power plant to solve the problems raised by the above-mentioned background technology.

[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] The present invention provides an anti-corrosion coating for a cooling tower of a power plant, the coating comprising a component A and a component B, the component A comprising a bisphenol A type liquid epoxy resin, a siloxane-modified waterborne epoxy resin dispersion, a modified amine curing agent, talcum powder, a dispersant, a leveling agent, and titanium dioxide;

[0008] The component B comprises nano filler, silane coupling agent and polyether amine;

[0009] The component A and the component B are uniformly mixed in a mass ratio of 1:0.2-0.25.

[0010] Furthermore, the component A comprises 50-60 parts by weight of bisphenol A liquid epoxy resin, 15-20 parts by weight of siloxane-modified waterborne epoxy resin dispersion, 10-15 parts by weight of modified amine curing agent, 15-20 parts by weight of talcum powder, 0.2-1 parts by weight of dispersant, 1.2-1 parts by weight of leveling agent and 10-15 parts by weight of titanium dioxide.

[0011] Furthermore, the nanofiller in component B is flaky graphene oxide particles.

[0012] Furthermore, the silane coupling agent in the component B is KH550 silane coupling agent, and the nanofiller, silane coupling agent and polyetheramine are mixed in a mass ratio of 1-2:0.2-1:0.2-1.

[0013] Further, the component B is prepared by the following steps:

[0014] S11, thoroughly washing the graphene oxide flakes to remove impurities and adsorbents on the surface;

[0015] S12, drying the cleaned graphene oxide flakes to prevent moisture and other impurities from affecting subsequent processes;

[0016] S13, adding a silane coupling agent uniformly to the surface of the flake graphene oxide, ensuring that the silane coupling agent can fully cover the surface of the flake graphene oxide and avoiding the formation of lumps and bubbles as much as possible;

[0017] S14, adding polyetheramine to the flake graphene oxide modified with a silane coupling agent;

[0018] S15, washing the finished product to remove unreacted polyetheramine and other impurities, and drying the finished product to ensure its stability.

[0019] Furthermore, in S12, the silane coupling agent is diluted to a concentration of 5%-8%, and stirred at a temperature of 60-80 degrees for 40 minutes, so that the silane coupling agent reacts chemically with functional groups such as hydroxyl groups on the surface of the flaky graphene oxide to form a strong chemical bond.

[0020] Furthermore, in S13, the polyetheramine and the flaky graphene oxide modified by a silane coupling agent are stirred at a temperature of 80-90 degrees for 12-15 hours to promote the reaction of the polyetheramine with the flaky graphene oxide or the silane coupling agent to form a new chemical bond or enhance the existing interface bonding force.

[0021] Further, the component A is prepared by the following steps:

[0022] S21, adding bisphenol A type liquid epoxy resin, siloxane modified waterborne epoxy resin dispersion and dispersant into a reaction kettle and uniformly mixing them at a speed of 150 to 300 rpm;

[0023] S22, then add the leveling agent, talcum powder and titanium dioxide in sequence at a speed of 200 to 400 rpm, stir evenly, add the modified amine curing agent, and finally stir at a speed of 1000 to 1500 rpm for 60 to 90 minutes.

[0024] Compared with the prior art, the present invention has the following advantages: In the present invention, silane coupling agent and polyetheramine are used to synergistically modify flaky graphene oxide to improve its dispersibility, and the modified graphene oxide is used as a filler to modify a waterborne epoxy resin coating, and the prepared coating has excellent anti-corrosion performance. DETAILED DESCRIPTION

[0027] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0028] Furthermore, the terms “first” and “second” are used for descriptive purposes only and should not be understood as indicating or implying relative importance.

[0029] In addition, in the description of the present invention, unless otherwise clearly defined, the terms "installed", "connected", "connected", and "connector" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood in combination with specific circumstances.

[0030] The present invention will be described in detail below with reference to embodiments and comparative examples.

[0031] Example 1

[0032] The anticorrosive coating includes component A and component B. Component A includes bisphenol A liquid epoxy resin, siloxane-modified waterborne epoxy resin dispersion, modified amine curing agent, talcum powder, dispersant, leveling agent, titanium dioxide; component B includes nano filler, silane coupling agent and polyether amine;

[0033] Component A includes 50 parts by weight of bisphenol A liquid epoxy resin, 15 parts by weight of siloxane-modified waterborne epoxy resin dispersion, 10 parts by weight of modified amine curing agent, 15 parts by weight of talcum powder, 0.2 parts by weight of dispersant, 1.2 parts by weight of leveling agent and 10 parts by weight of titanium dioxide.

[0034] The nanofiller in component B is flaky graphene oxide particles. The silane coupling agent in component B is KH550 silane coupling agent, and the nanofiller, the silane coupling agent and the polyetheramine are mixed in a mass ratio of 1:0.2:0.2.

[0035] Component B is prepared by the following steps:

[0036] S11, thoroughly washing the graphene oxide flakes to remove impurities and adsorbents on the surface;

[0037] S12, drying the cleaned graphene oxide flakes to prevent moisture and other impurities from affecting subsequent processes;

[0038] S13, adding a silane coupling agent uniformly to the surface of the flake graphene oxide, ensuring that the silane coupling agent can fully cover the surface of the flake graphene oxide and avoiding the formation of lumps and bubbles as much as possible;

[0039] S14, adding polyetheramine to the flake graphene oxide modified with a silane coupling agent;

[0040] S15, washing the finished product to remove unreacted polyetheramine and other impurities, and drying the finished product to ensure its stability.

[0041] In S12, the silane coupling agent is diluted to a concentration of 5%, and stirred at a temperature of 60-80 degrees for 40 minutes, so that the silane coupling agent reacts chemically with functional groups such as hydroxyl groups on the surface of the flaky graphene oxide to form a strong chemical bond.

[0042] In S13, the polyetheramine and the flaky graphene oxide modified by the silane coupling agent are stirred at a temperature of 80 degrees for 12 seconds to promote the reaction between the polyetheramine and the flaky graphene oxide or the silane coupling agent to form a new chemical bond or to enhance the existing interface bonding force.

[0043] Component A is prepared by the following steps:

[0044] S21, adding bisphenol A liquid epoxy resin, siloxane-modified waterborne epoxy resin dispersion, and dispersant into a reaction kettle and uniformly mixing them at a rotation speed of 150 rpm;

[0045] S22, then add the leveling agent, talcum powder and titanium dioxide in sequence at a speed of 200 rpm, stir evenly, add the modified amine curing agent, and finally stir at a speed of 1000 rpm for 60 minutes.

[0046] Finally, component A and component B were uniformly mixed in a mass ratio of 1:0.2.

[0047] Embodiment 2

[0048] The anticorrosive coating includes component A and component B. Component A includes bisphenol A liquid epoxy resin, siloxane-modified waterborne epoxy resin dispersion, modified amine curing agent, talcum powder, dispersant, leveling agent, titanium dioxide; component B includes nano filler, silane coupling agent and polyether amine;

[0049] Component A includes 60 parts by weight of bisphenol A liquid epoxy resin, 20 parts by weight of siloxane-modified waterborne epoxy resin dispersion, 15 parts by weight of modified amine curing agent, 20 parts by weight of talcum powder, 1 part by weight of dispersant, 1 part by weight of leveling agent and 15 parts by weight of titanium dioxide.

[0050] The nanofiller in component B is flaky graphene oxide particles. The silane coupling agent in component B is KH550 silane coupling agent, and the nanofiller, the silane coupling agent and the polyetheramine are mixed in a mass ratio of 2:1:1.

[0051] Component B is prepared by the following steps:

[0052] S11, thoroughly washing the graphene oxide flakes to remove impurities and adsorbents on the surface;

[0053] S12, drying the cleaned graphene oxide flakes to prevent moisture and other impurities from affecting subsequent processes;

[0054] S13, adding a silane coupling agent uniformly to the surface of the flake graphene oxide, ensuring that the silane coupling agent can fully cover the surface of the flake graphene oxide and avoiding the formation of lumps and bubbles as much as possible;

[0055] S14, adding polyetheramine to the flake graphene oxide modified with a silane coupling agent;

[0056] S15, washing the finished product to remove unreacted polyetheramine and other impurities, and drying the finished product to ensure its stability.

[0057] In S12, the silane coupling agent is diluted to a concentration of 8%, and stirred at a temperature of 80 degrees for 40 minutes, so that the silane coupling agent reacts chemically with functional groups such as hydroxyl groups on the surface of the flaky graphene oxide to form a strong chemical bond.

[0058] In S13, the polyetheramine and the flaky graphene oxide modified by the silane coupling agent are stirred at a temperature of 90 degrees for 15 hours to promote the reaction of the polyetheramine with the flaky graphene oxide or the silane coupling agent to form a new chemical bond or enhance the existing interface bonding force.

[0059] Component A is prepared by the following steps:

[0060] S21, adding bisphenol A type liquid epoxy resin, siloxane modified waterborne epoxy resin dispersion and dispersant into a reaction kettle and uniformly mixing them at a speed of 300 rpm;

[0061] S22, then add the leveling agent, talcum powder and titanium dioxide in sequence at a speed of 400 rpm, stir evenly, add the modified amine curing agent, and finally stir at a speed of 1000-1500 rpm for 90 minutes.

[0062] Finally, component A and component B were uniformly mixed in a mass ratio of 1:0.25.

[0063] Comparative Example 1

[0064] The anti-corrosion coating includes component A and component B. Component A includes bisphenol A liquid epoxy resin, siloxane-modified waterborne epoxy resin dispersion, modified amine curing agent, talcum powder, dispersant, leveling agent, and titanium dioxide. Component A includes 50 parts by weight of bisphenol A liquid epoxy resin, 15 parts by weight of siloxane-modified waterborne epoxy resin dispersion, 10 parts by weight of modified amine curing agent, 15 parts by weight of talcum powder, 0.2 parts by weight of dispersant, 1.2 parts by weight of leveling agent, and 10 parts by weight of titanium dioxide.

[0065] The nanofiller in component B is flaky graphene oxide particles. The silane coupling agent in component B is KH550 silane coupling agent, and the nanofiller, the silane coupling agent and the polyetheramine are mixed in a mass ratio of 1:0.2:0.2.

[0066] Component A is prepared by the following steps:

[0067] S21, adding bisphenol A liquid epoxy resin, siloxane-modified waterborne epoxy resin dispersion, and dispersant into a reaction kettle and uniformly mixing them at a rotation speed of 150 rpm;

[0068] S22, then add the leveling agent, talcum powder and titanium dioxide in sequence at a speed of 200 rpm, stir evenly, add the modified amine curing agent, and finally stir at a speed of 1000 rpm for 60 minutes.

[0069] Finally, component A and component B were uniformly mixed in a mass ratio of 1:0.2.

[0070] Comparative Example 2

[0071] The anti-corrosion coating includes component A and component B. Component A includes bisphenol A liquid epoxy resin, siloxane-modified waterborne epoxy resin dispersion, modified amine curing agent, talcum powder, dispersant, leveling agent, and titanium dioxide. Component A contains 60 parts by weight of bisphenol A liquid epoxy resin, 20 parts by weight of siloxane-modified waterborne epoxy resin dispersion, 15 parts by weight of modified amine curing agent, 20 parts by weight of talcum powder, 1 part by weight of dispersant, 1 part by weight of leveling agent, and 15 parts by weight of titanium dioxide.

[0072] Component A is prepared by the following steps:

[0073] S21, adding bisphenol A type liquid epoxy resin, siloxane modified waterborne epoxy resin dispersion and dispersant into a reaction kettle and uniformly mixing them at a speed of 300 rpm;

[0074] S22, then add the leveling agent, talcum powder and titanium dioxide in sequence at a speed of 400 rpm, stir evenly, add the modified amine curing agent, and finally stir at a speed of 1000-1500 rpm for 90 minutes.

[0075] Finally, component A and component B were uniformly mixed in a mass ratio of 1:0.25.

[0076] The product testing structures of the above embodiments and comparative examples are shown in Table 1

[0077] Table 1 is as follows:

[0078]

[0079]

[0080] It can be concluded from Table 1 that the anti-corrosion coating for cooling towers in power plants proposed by the present invention has more excellent corrosion resistance and impact resistance.

[0081] In summary, silane coupling agent and polyether amine are used to synergistically modify flake graphene oxide to improve its dispersibility, and the modified graphene oxide is used as a filler to modify the water-based epoxy resin coating, and the prepared coating has excellent anti-corrosion properties.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An anti-corrosion coating for cooling towers in power plants, characterized in that: The coating comprises component A and component B, wherein component A comprises bisphenol A type liquid epoxy resin, siloxane-modified waterborne epoxy resin dispersion, modified amine curing agent, talcum powder, dispersant, leveling agent, and titanium dioxide; The component B comprises nano filler, silane coupling agent and polyether amine; The component A and the component B are uniformly mixed in a mass ratio of 1:0.2-0.

25.

2. The anti-corrosion coating for cooling tower of power plant according to claim 1, characterized in that: The component A comprises 50-60 parts by weight of bisphenol A liquid epoxy resin, 15-20 parts by weight of siloxane-modified waterborne epoxy resin dispersion, 10-15 parts by weight of modified amine curing agent, 15-20 parts by weight of talcum powder, 0.2-1 parts by weight of dispersant, 1.2-1 parts by weight of leveling agent and 10-15 parts by weight of titanium dioxide.

3. The anti-corrosion coating for cooling tower of power plant according to claim 1, characterized in that: The nanofiller in the component B is flaky graphene oxide particles.

4. The anti-corrosion coating for cooling tower of power plant according to claim 3, characterized in that: The silane coupling agent in the component B is KH550 silane coupling agent, and the nano filler, silane coupling agent and polyether amine are mixed in a mass ratio of 1-2:0.2-1:0.2-1.

5. The anti-corrosion coating for cooling tower of power plant according to claim 4, characterized in that: The component B is prepared by the following steps: S11, thoroughly washing the graphene oxide flakes to remove impurities and adsorbents on the surface; S12, drying the cleaned graphene oxide flakes to prevent moisture and other impurities from affecting subsequent processes; S13, adding a silane coupling agent uniformly to the surface of the flake graphene oxide, ensuring that the silane coupling agent can fully cover the surface of the flake graphene oxide and avoiding the formation of lumps and bubbles as much as possible; S14, adding polyetheramine to the flake graphene oxide modified with a silane coupling agent; S15, washing the finished product to remove unreacted polyetheramine and other impurities, and drying the finished product to ensure its stability.

6. The anti-corrosion coating for cooling tower of power plant according to claim 5, characterized in that: In S12, the silane coupling agent is diluted to a concentration of 5%-8%, and stirred at a temperature of 60-80 degrees for 40 minutes, so that the silane coupling agent reacts chemically with functional groups such as hydroxyl groups on the surface of the flaky graphene oxide to form a strong chemical bond.

7. The anti-corrosion coating for cooling tower of power plant according to claim 5, characterized in that: In S13, the polyetheramine and the flaky graphene oxide modified by the silane coupling agent are stirred at a temperature of 80-90 degrees for 12-15 hours to promote the reaction of the polyetheramine with the flaky graphene oxide or the silane coupling agent to form a new chemical bond or enhance the existing interface bonding force.

8. The anti-corrosion coating for cooling tower of power plant according to claim 1, characterized in that: The component A is prepared by the following steps: S21, adding bisphenol A type liquid epoxy resin, siloxane modified waterborne epoxy resin dispersion and dispersant into a reaction kettle and uniformly mixing them at a speed of 150 to 300 rpm; S22, then add the leveling agent, talcum powder and titanium dioxide in sequence at a speed of 200 to 400 rpm, stir evenly, add the modified amine curing agent, and finally stir at a speed of 1000 to 1500 rpm for 60 to 90 minutes.

Citation Information

Patent Citations

  • Epoxy graphene heavy corrosion-resistant coating, and preparation method and application thereof

    CN107739566A

  • Modified graphene oxide co-curing water-borne epoxy resin paint and preparation method thereof

    CN110054965A

  • Graphene anticorrosive coating and preparation method thereof

    CN113150650A

  • Water-based graphene-based composite anticorrosive paint and preparation method thereof

    CN115232530A

Cited By

  • Preparation method and application of water-based high-solid novel graphene zinc heavy anti-corrosion coating

    CN120005485A